2017
DOI: 10.4088/jcp.15m10591
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing Exercise to Health Education for Stimulant Use Disorder

Abstract: Objective To evaluate exercise as a treatment for stimulant use disorders. Method The STimulant Reduction Intervention using Dosed Exercise study was a randomized clinical trial conducted in nine residential addiction treatment programs across the United States from July 2010 to February 2013. Of 497 adults referred to the study, 302 met all eligibility criteria, including DSM-IV criteria for stimulant abuse and/or dependence, and were randomized to either a dosed exercise intervention (Exericse) or a health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Of the selected studies, 34 were experimental studies with randomized sampling [4,5,8,9,11,12,15,17,18,21,25,27,29,30,46,48,49,52,54,55,[59][60][61][63][64][65][68][69][70][71][74][75][76][77], while the rest were quasi-experimental [6,7,10,13,14,16,20,22,26,28,47,50,51,53,[56][57][58]62,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the selected studies, 34 were experimental studies with randomized sampling [4,5,8,9,11,12,15,17,18,21,25,27,29,30,46,48,49,52,54,55,[59][60][61][63][64][65][68][69][70][71][74][75][76][77], while the rest were quasi-experimental [6,7,10,13,14,16,20,22,26,28,47,50,51,53,[56][57][58]62,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Aerobic exercise was the most used type of program, finding 27 studies that used this type of exercise [4,5,7,8,[10][11][12][13]16,18,22,26,46,49,50,56,57,[59][60][61]67,[74][75][76][77][78][79]. In addition, 14 studies were found that used exercise programs related to body-mind practices, such as yoga, tai chi or qigong [9,15,21,[28][29][30]54,55,[64][65][66]70,71,73], 10 who used combined strength and aerobic exercise [6,17,20,27,32,47,48,52,68,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An intent-to-treat approach including all randomized participants was used. All missing UCTs (missed visit/dropout/lost-to-follow-up) were imputed as positive, a method that does not make the missing-at-random assumption and has been employed in substance use disorder treatment trials (Avants et al, 2000; Bickel et al, 1988; Budney et al, 2006; Johnson et al, 2007; Trivedi et al, 2017; Winhusen et al, 2014). A sensitivity analysis using various single imputation approaches was also performed to evaluate the impact of various deviations from the missing-at-random assumption.…”
Section: Methodsmentioning
confidence: 99%
“…treatment of schizophrenia improved symptoms and functional outcomes compared to cognitive therapy alone (Malchow et al, 2016;Nuechterlein et al, 2016). In addition, stimulant users report more abstinent days when they participate in exercise combined with therapy compared to therapy partnered with health education (Trivedi et al, 2017).…”
Section: Acute Aerobic Exercise As a Priming Technique For Cognitive mentioning
confidence: 98%